1976
DOI: 10.1172/jci108305
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon response to hypoglycemia in sympathectomized man.

Abstract: A B S T R A C T Hypoglycemia stimulates immunoreactive glucagon (IRG) secretion and increases the activity of the sympathetic nervous system. To ascertain if the augmented alpha cell activity evoked by glucopenia is mediated by the adrenergic nervous system, the glucagon response to insulin-induced hypoglycemia of five subj ects with neurologically complete cervical transections resulting from trauma, thereby disrupting their hypothalamic sympathetic outflow, was compared to six healthy volunteers. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 26 publications
4
35
1
Order By: Relevance
“…In accordance with this, we have also found no glucagon response to hypoglycaemia in 10 Type 1 diabetic patients with autonomic neuropathy [24]. Several reports have demonstrated that the sympathetic nervous system is of minor or no importance for the glucagon response to hypoglycaemia [25,26]. Parasympathetic activity has been held responsible for glucagon release [24].…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with this, we have also found no glucagon response to hypoglycaemia in 10 Type 1 diabetic patients with autonomic neuropathy [24]. Several reports have demonstrated that the sympathetic nervous system is of minor or no importance for the glucagon response to hypoglycaemia [25,26]. Parasympathetic activity has been held responsible for glucagon release [24].…”
Section: Discussionsupporting
confidence: 88%
“…21 Spinal cord injury results in varying degrees of autonomic disturbances with eects also on metabolic regulation. Hypoglycaemia among subjects with high paraplegia and tetraplegia is accompanied by a reduction in blood pressure, absent increase of padrenaline 22 and noradrenaline 23 and lack of neuroglycopenic symptoms. In tetraplegic patients, mental arousal, cold or pain stimuli above lesion level do not cause any signiÂźcant cardiovascular response.…”
Section: Introductionmentioning
confidence: 99%
“…However, factors other than catecholamines must be capable of restoring normoglycemiiia because apparently normal glucose counterregulation has been observed in catecholamine-deficient patients with spinal cord transections (10,11), epinephrine-deficient adrenalectomized patients (11)(12)(13)(14), and normal subjects during the infusioIn of a-or ,-adrenergic blocking agents (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%